Development and Application of an Electrochemical Sensor for Hydroquinone in Pharmaceutical Products. Issue 15 (15th December 2020) - Cotchim, Suparat; Promsuwan, Kiattisak; Dueramae, Muslim; Duerama, Sophuwan; Dueraning, Anisah; Thavarungkul, Panote; Kanatharana, Proespichaya; Limbut, Warakorn
Abstract : In this work, a carboxylic acid-functionalized graphene (Gr-COOH)-modified glassy carbon electrode (GCE) (Gr-COOH/GCE) was developed and applied for the sensitive determination of hydroquinone in pharmaceutical products. Gr-COOH on a GCE was used as an adsorbent in adsorptive anodic stripping voltammetry (AdASV). Scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR), cyclic voltammetry (CV) and AdASV were employed to characterize the surface morphology and electrochemical behavior of the Gr-COOH/GCE. The sensitivity of the Gr-COOH/GCE was 3, 7, and 10 times higher than those of a Gr/GCE, GCE-COOH and bare GCE, respectively. Several operational parameters, including the amount of Gr-COOH, preconcentration potential and preconcentration time, were optimized. Under optimum conditions, the peak current response linearly increased with the hydroquinone concentration in the range of 0.1–40.0 μ mol l −1 (r = 0.999) with a high sensitivity of 19.86 μ A ( μ mol l −1 ) −1 cm −2 and a limit of detection of 0.04 μ mol l −1 . This proposed modified electrode exhibited good repeatability, accuracy and precision. It also showed good anti-interference properties. This method was successfully applied to detect hydroquinone in skin-lightening products.